THE RELATIONSHIP BETWEEN PARTICIPATORY LEADERSHIP STYLE AND WORK DISCIPLINE TO EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC - Yohan Antoni Simanjuntak; Suzanna Josephine LTobing; Frangky Sitorus (Fundamental Management Journal, 2023)
Research results indicates that (1) theres as a intercourse betweens command style and employee performance, the ranks spearmans correlations coefficienti is 0.350, whichs means thats the intercourse betweens there 2 variables is weak and has a positive value a lso artificial significance 0.023 smaller than 0.005. So, based on calculations, its cans be concluded thats there are. Theres as a significants intercourse betweens the variables of participatory command styles and the performance of subordinates 2 theres is a intercourse betweens discipline be at work and employe performance. The correlations coefficient of ranks spearman as 0.453, whichs mean thats the intercourse betweens the 2 variables as quites strongs and has a positive value and the results obtained are 0.003 less thans 0.05 with Thuis the results ofc this calculation cans be concludide thats there is a significants intercourse betweens discipline be at work variables an employet performance. Keywords: participatory leadership style, discipline be at work and employee performance.